PENGARUH KARAKTERISTIK PERUSAHAAN, CAPITAL INTENSITY, DAN INVENTORY INTENSITY TERHADAP AGRESIVITAS PAJAK - Stefanie Edeline; Ngadiman Ngadiman (Jurnal Paradigma Akuntansi, 2023)
This research aims to determine the effect of profitability, firm size, capital intensity, and inventory intensity on tax aggressiveness in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2017-2019. Determination of the sample using purposive sampling method and obtained data as many as 246 samples with 82 companies that meet the criteria for selecting the sample were observed for 3 consecutive years. The analysis method of this research uses multiple linear regression analysis which is assisted by using the Eviews version 12 program to process the data. The results of this study indicate that profitability and inventory intensity have a significant negative effect on tax aggressiveness. Meanwhile, the variables of firm size and capital intensity do not show a significant effect on tax aggressiveness.